Rubella sero-prevalence among children in Kilimanjaro region: a community based study prior to the introduction of rubella vaccine in Tanzania - Chotta, Nikolas A. S. (Ital J Pediatr, 2017)
BACKGROUND: Childhood rubella infection is a mild, self-limiting illness. Rubella infection among pregnant women however, is a major public health concern. Depending on gestation age, it may result in fetal death, stillbirth or a new-born with congenital rubella syndrome (CRS). Maternal antibodies protect young infants from rubella infection and lifelong immunity is acquired by vaccination or post-rubella infection. This study aims at characterizing rubella infection and its epidemiology in the Kilimanjaro region, prior to the introduction of the rubella vaccine in Tanzania. METHODS: This was a population based cross-sectional study, covering all the seven districts in Kilimanjaro region, North-eastern Tanzania. The study population included children of 0 to 36 months of age and their mothers/primary caretakers. A multistage sampling method was used to obtain a representative sample of the children. Interviews were conducted using a structured questionnaire. Dried blood spot (DBS) samples were taken from eligible children. Rubella specific IgG antibodies were detected from eluted serum by enzyme-linked immunosorbent assay (ELISA). Descriptive statistics were used to summarize the data, the difference between groups was tested by Fishers exact test or chi square test as appropriate. Univariate and multivariate analysis was used, with rubella sero-positive groups as dependent variables and the socio-demographic, children, paediatric and parental factors as independent variables, the Odds ratio and their 95% confidence intervals were calculated to assess the strength of association between the dependent and independent variables. A p value less than 0.05 was considered significant. RESULTS: The overall rubella sero-prevalence was 1.8%. Rural residence was associated with greater risk for rubella infection. Other family characteristic did not predict rubella infection. CONCLUSIONS: This study highlights the low natural immunity to rubella among children prior to the introduction of rubella vaccine in Tanzania. Our research underscores the need for an effective rubella vaccination program to prevent CRS. More epidemiologic and immunologic studies are needed to guide the vaccination deployment and administration strategy in Tanzania. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13052-017-0379-3) contains supplementary material, which is available to authorized users.